Rufus Saxton correspondence - Saxton, Rufus, 1824-1908.
ALS (1862 October 22) written by Saxton to the Board of Home Missions requesting the assignment of a military chaplain; ALS (1863 June 18) to George Whipple of the American Missionary Association expressing Saxton's appreciation upon receiving life membership in the organization; and ALS (1889 June 14) to John M. Burt reflecting Saxton's patriotism.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Burt, John Mowlem, -- Sir, -- 1845-1918 -- Correspondence; Whipple, George, -- 1805-1876 -- Correspondence; American Missionary Association; General Council of the Congregational and Christian Churches of the United States. -- Board of Home Missions; Patriotism; United States -- History -- Civil War, 1861-1865 -- Chaplains; Army officers